Multifactorial case of ascites and anemia in a Golden Retriever involving Babesia sp. and Toxocara canis infections - Septi, Dyanitha Yustina; Putu Ayu Sisyawati, Putriningsih; I Gusti Made Krisna, Erawan (ARSHI Veterinary Letters, 2024)
A seven-year-old male Golden Retriever presented with lethargy, anorexia, abdominal enlargement, and weakness. Hematology tests revealed lymphocytosis, microcytic hypochromic anemia with anisocytosis, hypoalbuminemia, hyperglobulinemia, and elevated levels of alkaline phosphatase (ALP), blood urea nitrogen (BUN), and creatinine. Radiographic examination showed pneumonia, an abnormal heart shape resembling an inverted "D," and fluid accumulation in the abdominal cavity. Blood smears indicated a Babesia sp. infection. Additionally, the dog expelled a worm identified as Toxocara canis. The complex interaction between T. canis infection, multiple organ dysfunction, Babesia sp. infection, and malnutrition contributed to the development of ascites and anemia in this case. Treatment included abdominocentesis and fluid therapy. The dog was also prescribed furosemide, methylprednisolone, digoxin, Hematodin®, VipAlbumin®, and Drontal® for the worm infection. Unfortunately, the dog died on the 5th day of treatment due to dehydration and worsening anemia.